Si celebrano i 50 anni della International Cartographic Association - Bernardini, Fulvio (GEOmedia, 2009)
International Cartographic Association's 50 years celebrations The International Cartographic Association (ICA) was born june 9th, 1959 in Bern, Switzerland. In the following decades the association progressively gained a central role between the organizations that deal with the universe of cartography. Nowadays, celebrating it's first 50 years of life, ICA is the leader organization for all the aspects connected to the discipline.